Hubungan Pengetahuan dan Sikap Ibu Perimenopause Terhadap Kesiapan Menghadapi Menopause - Norisa, Nanda; Fitriani, Aida; Asriah, Asriah; Novemi, Novemi (Jurnal Kebidanan Malakbi, 2022)
Along with increasing age, women often face various health problems. Problems that occur can be in the form of physical or psychological changes. One of them is the unpreparedness of women in the face of menopause. The Study of Women's Health Across the Nation (SWAN) in the United States show that menopause is associated with psychological stress, where as many as 28.9% experience stress in the early premenopause, 20.9% in the premenopausal stage, and as many as 22% experiences the postmenopausal stage. This study aims to determine whether there is a relationship between knowledge and attitudes of perimenopausal mothers on readiness to face menopause. This research uses mixed methods, where the research is quantitative and qualitative. Quantitative research is an analytic survey using a cross-sectional approach, while qualitative research by conducting in-depth interviews with the informants. Of the 62 respondents, 29 respondents (46.8%) who have less knowledge, and 24 (38.7%) of them were not ready to face menopause, with statistical test results obtained p-value 0.000 < sig_α=0.05. As much 37 respondents (59.7%) with a negative attitude, 28 respondents (45.2%) of them were not ready to face menopause, with statistical test results obtained p-value 0.000 < sig_α=0.05. There is a significant relationship between knowledge of perimenopausal mothers and readiness to face menopause. There is a significant relationship between the attitudes of perimenopausal mothers and the readiness to face menopause.